(untitled) (Research, Society and Development, 2021)
Self-medication is a habit adopted by individuals who often end up opting for this method in search of a quick relief for their ailments. In late 2019 SARS-CoV-2 was discovered after cases were reported in China, with reports that included mild and persistent respiratory symptoms characteristic of COVID-19. It is notable that against this backdrop, there has been a great deal of media influence for the use of medication as a supposed immediate treatment, despite no scientifically proven efficacy. The increase in self-medication is something historical throughout humanity, sick people who have little access to scientific studies and quality healthcare constantly opt for self-medication without a prescription. During the pandemic of the new coronavirus, several false news reports point to miracle drugs to treat the COVID-19 disease, but they are scientifically ineffective and poorly proven. The use of over-the-counter medications is a health risk for those who frequently adhere to these practices. This literature review article has the overall objective of identifying the reasons for self-medication during the coronavirus pandemic and the main risks of over-the-counter medication use.